Shenfu Injection Promotes Vasodilation by Enhancing eNOS Activity Through the PI3K/Akt Signaling Pathway In Vitro - Zhu, Jinqiang; Song, Wanshan; Xu, Shixin; Ma, Yan; Wei, Baoyu; Wang, Hongwu; Hua, Shengyu (Frontiers in Pharmacology, 2020)
Vasomotor dysfunction is one of the key pathological aspects of shock and heart failure (HF). Shenfu injection (SFI) has been widely used for the treatment of shock and HF in China. Pharmacological studies have suggested that SFI can reduce peripheral circulation resistance and improve microcirculation. However, whether it has a regulatory effect on macrovascular has not been elucidated. In this study, we used the thoracic aorta rings isolated from Wistar rats and the human umbilical vein cell line (EA.hy926) to explore the vasodilative activity of SFI and its potential mechanisms. The relaxation to SFI was measured after pre-treated with selective soluble guanylate cyclase (sGC) inhibitor or cyclooxygenase (COX) inhibitor and compared with the vasodilation effect of SFI only treated with norepinephrine (NE). The content of NO, endothelin-1 (ET-1), endothelial nitric oxide synthase (eNOS), COX-1, 6-K-PGF1α, and caveolin-1 were evaluated respectively. Besides, the level of eNOS mRNA, total eNOS and its phosphorylation were studied to investigate the potential mechanisms. Experimental results showed SFI markedly attenuated NE-induced vasoconstriction, but this effect was significantly eliminated after pre-incubation with the selective sGC inhibitor 1-H-[1, 2, 4] oxadiazolo [4, 3-] quinoxaline-1-one (ODQ), instead of the COX inhibitor indomethacin (INDO). SFI significantly increased the eNOS content and up-regulated the eNOS mRNA expression, while did not affect the content of COX-1 and 6-K-PGF1α. SFI also markedly increased NO content, but significantly reduced the content of ET-1 and caveolin-1 in the cell supernatant. Furthermore, it promoted the expression of total eNOS and the phosphorylation of eNOS at serine (Ser) 1177 but inhibited the phosphorylation at threonine (Thr) 495, which was significantly reversed by PI3K specific inhibitor LY294002. In conclusion, our study showed the SFI’s vasodilation in thoracic aorta is mediated entirely by enhancing eNOS activity through the PI3K/Akt signaling pathway, which provides a novel knowledge of SFI on shock and HF in future clinical application.